Glass article with easy clean coating

JP2025032203APending Publication Date: 2025-03-11NIPPON SHEET GLASS CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2024211751
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-08-21
Filing Date
2024-12-04
Publication Date
2025-03-11

AI Technical Summary

Benefits of technology

【0008】 本発明によれば、改善されたイージークリーン性を有するコーティング付きガラス物品が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025032203000001_ABST
    Figure 2025032203000001_ABST
Patent Text Reader

Abstract

To provide a glass article with coating having improved easy clean coating property.SOLUTION: A coated glass article includes a glass substrate and an easy clean coating on the glass substrate, wherein the coating contains cerium oxide, and the coating is either a single-layer film or a multilayer film, and when it is the multilayer film, it includes a layer containing cerium oxide as the top layer, with a water contact angle on the surface of the coating being between 60° and 130°, and corresponding to at least one selected from the group consisting of window glass, roof glass, bathroom glass, mirrors, commercial glass, glass for mobile devices, and glass for solar cells.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to glass articles with an easy-clean coating. [Background technology]

[0002] A coating called an easy-to-clean coating may be formed on the surface of various substrates. The easy-to-clean coating makes it easier to remove dirt adhering to the surface of the substrate. The easy-to-clean coating typically contains a fluorine-containing organic compound. A typical substrate on which the easy-to-clean coating is formed is a glass substrate. For example, a commercially available coating liquid containing a fluoroalkyl group-containing silicon alkoxide is applied to the surface of the glass substrate to form the easy-to-clean coating.

[0003] Patent Document 1 discloses a technique of providing an adhesion promoter layer between a glass substrate and an easy-clean coating. The adhesion promoter layer is specifically a silicon mixed oxide layer, which improves the durability of the easy-clean properties. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2014-522433 Summary of the Invention [Problem to be solved by the invention]

[0005] In conventional easy-clean coatings, the adhesion of dirt is suppressed by the high water repellency of the fluorine-containing organic compound. However, according to the investigations of the present inventors, there is room for improvement in the easy-cleanability of the fluorine-containing organic compound.

[0006] The present invention aims to provide a coated glass article with improved easy-clean properties. [Means for solving the problem]

[0007] The present invention relates to A glass substrate and an easy-clean coating on the glass substrate, the coating comprises cerium oxide; The contact angle of water on the surface of the coating is 60° to 130°. A coated glass article is provided. Effect of the Invention

[0008] SUMMARY OF THE PRESENT DISCLOSURE In accordance with the present invention, coated glass articles are provided that have improved easy-clean properties. [Brief description of the drawings]

[0009] [Figure 1] 1A to 1C are schematic cross-sectional views illustrating the progress of evaporation of a water droplet on a hydrophilic surface. [Diagram 2] FIG. 2 is a schematic cross-sectional view illustrating the progress of evaporation of a water droplet on a surface to which water repellency has been imparted by a fluorine-containing organic compound. [Diagram 3] FIG. 2 is a diagram showing the results of observing the coated glass article produced in Example 1 with a scanning electron microscope (SEM). [Figure 4] FIG. 2 is a diagram showing the results of SEM observation of the coated glass article produced in Example 2. [Diagram 5] FIG. 1 shows the results of SEM observation of the coated glass article produced in Example 4. [Figure 6] FIG. 13 is a diagram showing the results of SEM observation of the coated glass article produced in Example 5. [Figure 7] FIG. 13 is a diagram showing the results of observation of tap water in a stain adhesion test carried out in Example 10. [Figure 8]FIG. 1 shows the results of a stain adhesion test / tap water observation carried out in Example 11. [Figure 9] FIG. 13 is a diagram showing the results of observation of tap water in a dirt adhesion test carried out in Comparative Example 4. [Figure 10] FIG. 13 is a diagram showing the observation results of a stain adhesion test / tap water carried out in Comparative Example 5. [Figure 11A] FIG. 13 is a diagram showing the results of the stain adhesion test performed in Example 12 / observation of the hand soap before rinsing with running water. [Figure 11B] FIG. 13 shows the results of the stain adhesion test performed in Example 12 / observation of the hand soap after rinsing with running water. [Figure 12A] FIG. 13 is a diagram showing the results of observation of a stain adhesion test / hand soap before rinsing with running water performed in Comparative Example 6. [Figure 12B] FIG. 13 is a diagram showing the results of the stain adhesion test / observation after rinsing with hand soap with running water performed in Comparative Example 6. [Figure 13A] FIG. 13 is a diagram showing the results of observation of a stain adhesion test / hand soap before rinsing with running water performed in Comparative Example 7. [Figure 13B] FIG. 13 is a diagram showing the results of the stain adhesion test / observation after rinsing with hand soap with running water performed in Comparative Example 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The following description of the embodiments of the present invention is not intended to limit the present invention to a specific form. In this specification, "main component" means a component with a content of 50% or more, particularly 60% or more, by mass. "Substantially free" means a content of less than 1%, further less than 0.1%, by mass. "Substantially flat" means that no irregularities with a height or depth of 500 nm or more are observed, except for fine particles and fine particle-like protrusions on the surface, when observed with an SEM. "Room temperature" is used as a term meaning a temperature in the range of 5 to 35°C, particularly 10 to 30°C.

[0011] The coated glass article provided by this embodiment comprises: A glass substrate and an easy-clean coating on the glass substrate, the coating comprises cerium oxide; The contact angle of water on the surface of the coating is 60° to 130°.

[0012] The coated glass article provided by this embodiment has, for example, A step of applying a coating liquid containing cerium oxide as a solid content or a coating liquid containing chelated cerium ions onto a glass substrate to form a coating film on the glass substrate; and drying the coating to form an easy-clean coating. The cerium oxide is CeO 2 The present invention can be provided by a manufacturing method comprising the steps of:

[0013] Up until now, it has been assumed that the height of the contact angle of water is a measure of the easy-cleaning property of easy-clean coatings. For this reason, the coating materials used have been organic materials that can achieve a high contact angle, such as fluorine-containing organic compounds. However, in reality, on a surface that has been given water repellency by fluorine-containing organic compounds, scattered stains tend to remain as water droplets attached thereon evaporate. These stains are formed when the fine particles or solutes contained in the attached water droplets gather in spots in a small area. Even on glass surfaces on which no coating is formed, uneven distribution of stains is often observed. Ring-shaped stains remaining on hydrophilic glass surfaces are sometimes called "coffee rings." Spot- or ring-shaped stains that remain concentrated are easily noticeable, and depending on the degree of concentration, they may not be easily removed.

[0014] The mechanism by which stains remain in a ring shape can be understood from FIG. 1. A water droplet 10 attached to a hydrophilic surface 21 of a glass substrate 20 shrinks as the water evaporates, and eventually disappears. During evaporation, the water droplet 10 tends to shrink while maintaining the contact area with the hydrophilic surface 21. For this reason, the center of the water droplet 10 shrinks more than the periphery. As this shrinkage occurs, a flow 31 is generated inside the shrinking water droplet 11 near the surface 21 of the substrate 20, flowing from the center toward the periphery 11p. This minute flow 31 causes foreign matter contained in the water droplet 11 and fine particles, which are precipitated solutes, to gather at the periphery 11p and precipitate in a ring shape.

[0015] The mechanism by which stains remain in spots can be understood from FIG. 2. A water droplet 10 attached to a water-repellent surface 22 of a glass substrate 20 shrinks as the water evaporates, and eventually disappears. On the surface 22 to which water repellency has been imparted by a fluorine-containing organic compound, the water droplet 10 tends to shrink while maintaining a high contact angle with the surface 22. As a result, inside the water droplet 10 that shrinks into a smaller water droplet 11, a flow 32 is generated near the surface 22 of the substrate, moving from the periphery toward the center 11c. This minute flow 32 causes the fine particles contained in the water droplet to gather in the center 11c and precipitate in the form of a spot.

[0016] Surprisingly, it was found that on a coating containing cerium oxide and having a water contact angle of 60° to 130°, particularly 70° to 110°, dirt that appears as water droplets evaporate tends not to concentrate. In other words, on this coating, the tendency of dirt originating from water droplets to adhere unevenly to a specific area after evaporation of the water droplets is alleviated. It was also confirmed that dirt that adheres relatively widely on this coating is easier to remove than dirt that adheres in a concentrated manner. The coated glass article according to this embodiment can alleviate the uneven distribution of dirt that adheres, thereby improving easy-to-clean properties. On a surface that has been given water repellency by a fluorine-containing organic compound so that the water contact angle is the same as above, 60° to 130°, dirt remains in spots. Considering this point, it is believed that not only the contact angle but also the cerium oxide contributes to the expression of easy-to-clean properties according to this embodiment. Furthermore, the coated glass article according to this embodiment also makes it easier to wash off attached organic matter. It is believed that cerium oxide also contributes to improving the easy-cleaning properties of the coating against attached organic matter.

[0017] Unlike aluminum oxide, silicon oxide, etc., cerium oxide can function as a water-repellent material. According to the inventor's study, the water repellency of cerium oxide can reach 75° or more, 80° or more, and even 85° or more, as expressed by the contact angle of water. Until now, such a contact angle has been achieved by surface treatment using an organic water repellent. Organic water repellents usually decompose in the process of heating up to about 300°C, but cerium oxide remains stable even when heated to higher temperatures.

[0018] In this embodiment, the contact angle of water on the surface of the coating after the glass article is subjected to a heat treatment at 760° C. for 4 minutes may be 60° to 130°, particularly 70° to 110°. The contact angle of water after the heat treatment may reach 75° or more, 80° or more, or even 85° or more. However, in this embodiment, the contact angle of water on the surface of the coating may be measured after a period of time has elapsed since the heat treatment, since the contact angle may temporarily decrease immediately after the heat treatment. The contact angle may take several tens of days to recover. Thus, the contact angle may be measured, for example, after the glass article is subjected to a heat treatment at 760° C. for 4 minutes and then stored in air at room temperature for 40 days.

[0019] Below, we will explain the glass substrate and coating that constitute the coated glass article of this embodiment, then we will explain the properties that can be achieved by this embodiment and uses of the article, and finally we will explain the manufacturing method of this embodiment.

[0020] (Glass substrate) There is no particular limitation on the type of glass constituting the glass substrate. The glass substrate may be made of various types of glass called soda-lime glass, borosilicate glass, aluminosilicate glass, alkali-free glass, quartz glass, etc. The glass substrate is made of SiO 2 The glass substrate may be mainly composed of the above. There is no particular limitation on the size and shape of the glass substrate. The glass substrate may be a glass plate, a glass container, a glass lid, a glass tube, a glass bulb, a glass lens, or other molded body. The glass container may be, for example, a glass vial, a glass ampoule, or a glass bottle, but may also have other shapes such as trays and petri dishes. The glass lid is not limited in shape as long as it functions as a lid, and may have a shape that can be used as a lid for a cookware, for example.

[0021] The glass plate may be flat, or may have a curved shape imparted by bending processing. The thickness of the glass plate is not particularly limited, but is, for example, within the range of 0.5 to 12 mm. The glass plate may be treated so as to be suitable for use as window glass for buildings, vehicles, etc. The glass plate may be, for example, tempered. In other words, the glass plate may be tempered glass. Known tempering processes include air-cooling tempering, which generates a compressive stress layer on the surface by heating and then quenching, and chemical tempering, which generates a compressive stress layer on the surface by ion exchange of alkali metal ions. The glass plate may be integrated with another glass plate by lamination processing and / or multi-layer processing. A coating may be formed on the surface of the glass plate to impart or control properties other than water repellency. Examples of the coating include a Low-E film, a conductive film, an anti-reflection film, and a colored film. The colored film is, for example, a ceramic coating. The ceramic coating is formed to impart decorativeness, make a part of the glass plate opaque, and the like.

[0022] Many of the above-mentioned treatments of glass sheets involve heating the glass sheets. For example, bending of glass sheets includes a process of heating and softening the glass sheets. In addition to the tempering process, lamination processing and multi-layer processing may also involve heating the glass sheets to high temperatures depending on the type of resin film sandwiched between the glass sheets or the sealant used to seal the space between the glass sheets. After undergoing these heating processes, the water repellency of the easy-clean coating made of organic matter is greatly reduced and the easy-clean property is also impaired. For this reason, it was necessary to form the coating after the process involving heating the glass sheets. Such process restrictions may hinder the efficiency of mass production. For example, it is much more difficult to uniformly apply a coating liquid to a curved surface than to apply it to the surface of a flat plate. The process of applying a coating liquid to flat ribbon-shaped glass before it is cut and processed to have individual curved surfaces can be carried out much more efficiently.

[0023] The problem of the decrease in water repellency due to a treatment involving heating is not limited to glass plates, but occurs in glass substrates in general. In contrast, according to the present embodiment, the water repellency is expressed without relying on organic matter, so that the decrease in water repellency due to heating can be suppressed. Therefore, in the method according to the present embodiment, after forming a coating, the glass substrate on which the coating is formed can be heated to perform various treatments on the glass substrate. Examples of various treatments for a glass substrate include at least one selected from the group consisting of a bending treatment involving heating (heat bending treatment), an air-cooling tempering treatment, a chemical tempering treatment, a lamination treatment, a multi-layer processing treatment, and a coating formation treatment, particularly a heat bending treatment and / or an air-cooling tempering treatment. That is, in the present embodiment, the glass substrate may be a glass plate that has been subjected to at least one treatment selected from the group consisting of a heat bending treatment and an air-cooling tempering treatment. The temperature applied to the above heat treatments is usually at most about 760°C or less.

[0024] Conventionally, a glass sheet is cut into a predetermined shape, and then a heat bending process and / or an air-cooling tempering process are performed, and then a coating liquid for forming an easy-clean coating is applied to the main surface of the glass sheet. As a result, a part of the coating liquid adheres to the end surface of the glass sheet, and a coating is formed on at least a part of the end surface. In contrast, according to the present embodiment, a coating liquid is applied to the main surface of a flat glass sheet to form an easy-clean coating, and then at least one process selected from the group consisting of a heat bending process and an air-cooling tempering process can be performed on the glass sheet. The glass sheet provided by this embodiment can have a coating on at least one of its main surfaces, and no coating on the end surface of the glass sheet. A thick coating may be formed locally on the end surface where the coating liquid is likely to accumulate. Therefore, being able to avoid this is advantageous in terms of ensuring the aesthetic appearance of the product. In addition to improving the quality, the coating process can be continuously performed on a large-area glass sheet before cutting, which contributes to reducing the cost of the final product.

[0025] (coating) The easy-clean coating contains cerium oxide. The coating may contain cerium oxide in an amount of 10 mass % or more, 30 mass % or more, or may further contain cerium oxide as a main component. The coating may be a film that is substantially free of components other than cerium oxide. The coating may have a surface on which cerium oxide is exposed. The cerium oxide is CeO 2 , i.e., oxide of tetravalent cerium. CeO 2 Ce 2 O 3 In other words, it is a more desirable component from the viewpoint of improving the ease of cleaning than trivalent cerium oxide. However, the coating contains Ce as cerium oxide. 2 O 3 For example, when a compound containing trivalent cerium is used as a cerium oxide source and a part of it is oxidized to tetravalent cerium, CeO 2 The remaining trivalent cerium is Ce 2 O 3 is included in the coating as

[0026] Easy-clean coatings on substrates such as glass usually have a multilayer structure consisting of a metal oxide layer that provides a base and an overcoat layer of an organic compound. The overcoat layer is often composed of a hydrolysis polycondensate of a hydrolyzable organosilicon compound in order to strongly bond with the metal oxide layer. The hydrolyzable organosilicon compound is an organic compound suitable for improving water repellency, typically a fluoroalkyl group-containing compound. In contrast, in this embodiment, the coating may be substantially free of a hydrolysis polycondensate of a hydrolyzable organosilicon compound. In addition, the coating may be substantially free of a fluorine-containing organic compound, particularly a fluoroalkyl group-containing compound.

[0027] The coating may be a single layer or a multi-layered film composed of multiple layers, but a single layer is advantageous in terms of reducing mass production costs. The easy-clean coating of this embodiment can provide easy-clean properties even if it is a single layer. In the case of a multi-layered film, the coating desirably has a layer containing cerium oxide as the uppermost layer of the multi-layered film. In other words, in this embodiment, an underlayer may be interposed between the glass substrate and the coating. The underlayer may be, for example, a metal oxide layer, and specifically, may be a layer having a lower mass-based content of cerium oxide than the surface coating, or may even be a layer that is substantially free of cerium oxide. The underlayer may contain at least one selected from the group consisting of silicon oxide, aluminum oxide, zirconium oxide, and titanium oxide. One example of a desirable underlayer is a layer mainly composed of silicon oxide. The underlayer may itself be multiple layers. The underlayer, which is a multi-layered film, may be, for example, a Low-E film.

[0028] The easy-clean coating of this embodiment can provide a water contact angle of 60° or more, 65° or more, 70° or more, 75° or more, even 80° or more, 85° or more, and in some cases 90° or more. The upper limit of the water contact angle is not particularly limited, but is, for example, 130° or less, 120° or less, 110° or less, 105° or less, further 100° or less, or 95° or less. The water contact angle can be measured by dropping 4 mg (about 4 μL) of purified water onto the surface of the coating.

[0029] The easy-clean coating of the present embodiment does not completely lose its water repellency even when heated to high temperatures, such as 500° C. or even 760° C. The coating of the present embodiment may provide a water contact angle of 60° or more, 65° or more, 70° or more, 75° or more, even 80° or more, 85° or more, or even 90° or more, and 130° or less, 120° or less, 110° or less, 105° or less, or even 100° or less, 95° or less, even after exposing a glass article to a heat treatment at 760° C. for 4 minutes.

[0030] Although the details of the reason are unclear, the water repellency of the easy-clean coating of the present embodiment may temporarily decrease after being heated at high temperature. In addition, the measured value may be unstable and low immediately after film formation. However, even in these cases, the contact angle of water gradually increases and becomes stable to the above-mentioned level by simply exposing the coating to the atmosphere and storing it at room temperature. According to the study by the present inventors, the period required for recovery and stabilization is approximately 30 to 40 days. Therefore, it is preferable to measure the contact angle after heat treatment at high temperature after storing it in the atmosphere at room temperature for a predetermined period of time.

[0031] The easy-clean coating may contain an organic component. The organic component may be an organic compound or an organic group bonded to an oxide or the like that constitutes the film. The content of the organic component in the coating is not particularly limited, but may be 0.01% or more, or even 0.1% or more, and may be 10% or less, or even 1% or less, on a mass basis. A coating that has not been exposed to a high-temperature heat treatment may contain a relatively high content of organic components. However, the coating may be substantially free of organic components.

[0032] The organic group contained in the easy-clean coating may include an epoxy group. The epoxy group is a preferred functional group suitable for use in the manufacturing example described below. As described below, the epoxy group reacts with other components, specifically, with an acid, and is consumed, but the epoxy group added in excess may remain in the coating. The epoxy group remaining in the coating may function as a crosslinking agent, particularly during heat treatment, and may affect the structure of the film.

[0033] The easy-clean coating may contain inorganic compounds other than cerium oxide. Examples of oxides other than cerium oxide include silicon oxide, aluminum oxide, zirconium oxide, titanium oxide, ruthenium oxide, and oxides of rare earth elements other than cerium. Cerium oxide is easily available and inexpensive among rare earth oxides. The coating may not contain rare earth oxides other than cerium oxide. The inorganic compound may be a compound other than an oxide, such as a nitride or carbide.

[0034] The easy-clean coating has a thickness of, for example, 2 to 1000 nm, particularly 5 to 500 nm. The coating may have a thickness of 7 nm or more, or even 10 nm or more, and may have a thickness of 300 nm or less, or even 200 nm or less.

[0035] The easy-clean coating may have a dense structure, but may also have pores inside. The porosity of the coating may be, for example, 20% or more, 25% or more, 30% or more, or in some cases 40% or more, or 85% or less, 70% or less, 60% or less, or in some cases 50% or less. A coating with an appropriate porosity may have excellent optical properties. Specifically, by controlling the porosity, it is possible to eliminate interference colors that may occur due to the coating, improve visible light transmittance and reflectance, and the like.

[0036] The easy-clean coating may have a plurality of fine particles on its surface. The fine particles may be cerium oxide fine particles. In other words, the cerium oxide contained in the coating may be included as fine particles partly exposed on the surface of the film as fine particles. The surface of the coating may be substantially flat. As described above, whether or not the surface is substantially flat is determined based on the flatness of the surface excluding the fine particles, that is, excluding the unevenness imparted by the fine particles. The particle size of the cerium oxide fine particles may be in the range of 100 nm to 1.5 μm, or even 250 nm to 1 μm. The particle size of the fine particles can be measured by SEM observation. On the surface of the coating, the fine particles having the above particle size may be present at a density of 1 to 100 particles, or even 2 to 20 particles, per 5 μm square of the film surface. The presence of the fine particles may contribute to improving water repellency through the development of minute unevenness.

[0037] The crystallite size of the cerium oxide fine particles contained in the easy-clean coating is not particularly limited, and may be, for example, in the range of 1 to 100 nm, or further 2 to 20 nm.

[0038] When the glass substrate is a glass plate, the easy-clean coating may be formed on only one main surface of the glass plate or on both main surfaces of the glass plate, but in order to prevent a decrease in visible light transmittance, it is preferable to form the coating on only one main surface of the glass plate.

[0039] (characteristic) The water repellency that the glass article of the present embodiment can provide is as described above. In addition, the glass article of the present embodiment can have, for example, the following optical properties. The visible light transmittance may be 65% or more, 70% or more, 80% or more, or even 85% or more. The upper limit of the visible light transmittance is not particularly limited, but is, for example, 95%. The visible light reflectance may be 20% or less, 15% or less, 10% or less, or even 8% or less. The lower limit of the visible light reflectance is not particularly limited, but is, for example, 2%. Here, the visible light reflectance is the visible light reflectance of the surface on which the coating is formed, in other words, the reflectance of visible light that reaches the glass substrate from the outside of the glass article through the coating. The haze is, for example, 20% or less, but is preferably 10% or less, further 5% or less, and particularly 4% or less. According to the present embodiment, a haze of 1% or less, or even 0.5% or less can also be achieved.

[0040] The preferred ranges of the visible light transmittance, visible light reflectance and haze ratio are as follows. The ranges in parentheses are more preferred. Visible light transmittance: 80~95% (85~95%), Haze rate: 5% or less (4% or less), Visible light reflectance of the glass substrate surface on which the coating is formed: 2-20% (2-8%)

[0041] (Use of the item) The coated glass article according to the present embodiment may be used for various purposes, but is particularly suitable for use as a glass article used in an environment where water droplets are attached. The water droplets are usually supplied from natural water such as rain or fog, or tap water. The coated glass article according to the present embodiment may specifically be at least one article selected from the group consisting of architectural glass, transportation glass, store glass, furniture glass, home appliance glass, signage glass, mobile device glass, and solar cell glass. The coated glass article according to the present embodiment may be at least one article selected from the group consisting of window glass, roof glass, bathroom glass, mirror, store glass, mobile device glass, and solar cell glass. The window glass is, for example, a window glass of a building or a transportation aircraft, and the same is true for roof glass. The architectural structure is not limited to a house or building, but also includes a greenhouse, an arcade, and other structures fixed to the land. The transportation aircraft includes a vehicle, a ship, and an aircraft. The vehicle is, for example, an automobile or a railroad car. The bathroom glass is, for example, a glass partition and a glass door of a bathroom. The mirrors are, for example, mirrors in bathrooms and vanities. The store glass is, for example, show windows, counters, tables, glass doors of refrigerated or frozen cases, and showcases for food, etc. The mobile device glass is, for example, glass that covers the display unit of a mobile device such as a smartphone or a tablet PC, and in some cases, glass that constitutes the housing of a mobile device. The solar cell glass is, for example, a cover glass placed on the light incident side of a solar cell. In particular, when safety to the human body needs to be ensured, tempered glass is often used in each of the above-mentioned applications.

[0042] (Manufacturing method) Next, a method for producing the glass article of the present embodiment will be described, although the glass article of the present embodiment may be produced by a method other than the following production method.

[0043] The manufacturing method of this embodiment includes a step of applying a coating liquid containing cerium oxide as a solid content onto a glass substrate to form a coating film on the glass substrate, and a step of drying the coating film, and the cerium oxide is CeO 2 In addition, the "cerium oxide" as a solid content does not have to exist as a complete oxide as long as it is a component that can supply cerium oxide to the coating, and also includes cerium oxide hydroxide and cerium hydroxide that can supply cerium oxide after dehydration condensation.

[0044] This manufacturing method may further include a step of preparing a coating liquid. The coating liquid may contain a polar solvent, particularly a lower alcohol having 5 or less carbon atoms, as a solvent. The lower alcohol may be methanol and / or ethanol. The step of preparing the coating liquid may include hydrolyzing a cerium compound containing trivalent cerium. The hydrolyzable cerium compound is preferably a compound that dissolves in a polar solvent, and specifically may be selected from water-soluble cerium compounds. The cerium compound may be, for example, at least one selected from the group consisting of cerium halides and cerium nitrate. The cerium halide is, for example, cerium (III) chloride or cerium (III) bromide. As exemplified herein, including cerium (III) nitrate, a preferred cerium compound is a compound of trivalent cerium. However, the present invention is not limited thereto, and the cerium compound may contain tetravalent cerium.

[0045] In a general sol-gel method, an acid or alkali is added to the coating liquid to promote hydrolysis of the metal compound. In the manufacturing method of this embodiment, an acid or alkali may be added. However, a more preferred additive is an organic compound that functions as an acid scavenger, specifically an epoxy group-containing organic compound, particularly a water-soluble epoxide. The water-soluble epoxide is an epoxy group-containing compound having a solubility of 1 g / 100 mL or more in water at 20° C. The water-soluble epoxide may be a monofunctional epoxide or a polyfunctional epoxide. The monofunctional water-soluble epoxide may be, for example, an epoxy group-containing alkane such as propylene oxide (1,2-epoxypropane) or 1,2-epoxybutane, as well as lauryl alcohol EO adduct glycidyl ether, phenol EO adduct glycidyl ether, etc. The polyfunctional water-soluble epoxide is, for example, glycerol polyglycidyl ether, polyglycerol diglycidyl ether, or sorbitol polyglycidyl ether.

[0046] As described above, in the manufacturing method of this embodiment, the cerium compound is preferably hydrolyzed in the presence of a water-soluble epoxide. When the cerium compound is hydrolyzed in the presence of a water-soluble epoxide, the acid generated by the hydrolysis of the cerium compound is consumed, and the hydrolysis reaction is accelerated. In addition, in a coating liquid to which an excess of water-soluble epoxide is added, tetravalent cerium is easily generated from trivalent cerium. This phenomenon is considered to be due to the improved stability of tetravalent cerium in the high pH range.

[0047] The prepared coating liquid is applied onto a glass substrate by a known method such as spin coating, bar coating, spray coating, nozzle flow coating, or roll coating.

[0048] The manufacturing method of this embodiment may further include a step of subjecting the coating film to at least one treatment selected from washing and drying. The coating film in a wet state as applied contains organic compounds contained in the coating liquid, such as water-soluble epoxides and their ring-opening reaction products, together with cerium oxide. At least a part of the organic compounds in the coating film in a wet state is removed from the coating film by a treatment that is washing and / or drying, particularly washing. As the solvent used for washing, an organic solvent, particularly a polar organic solvent having 5 or less carbon atoms, is suitable. One preferred example of washing is carried out by sequentially using a lower alcohol and a ketone. Here, as described above, the lower alcohol is an alcohol having 5 or less carbon atoms. Preferred ketones are ketones having 7 or less, 5 or less, and even 3 or less carbon atoms. By removing the organic compound, pores are formed in the coating after drying, and micro-irregularities can be formed on the surface. The porosity and the size of the micro-irregularities can be controlled by the amount of organic compound added and other factors. The manufacturing methods exemplified above are particularly suitable for forming an easy-clean coating having a desired porosity and micro-irregularities.

[0049] The oxidation of trivalent cerium to tetravalent cerium may take time. Therefore, the manufacturing method of this embodiment may further include a step of holding at least one selected from the coating liquid and the coating film in a wet state for a predetermined time. This step can be carried out, for example, by holding at least one selected from the prepared coating liquid and the coating film in a wet state at a temperature of 5 to 80°C for 0.5 to 48 hours. This step allows the coating liquid or the coating film to undergo so-called "aging", and the ratio of tetravalent cerium increases. The coating liquid is preferably the subject to be aged. For example, as the conversion of the coating liquid to tetravalent cerium progresses, color development due to tetravalent cerium is observed. A coating liquid containing only trivalent cerium is colorless unless it contains other materials that cause coloring. As tetravalent cerium is produced, the coating liquid can typically be colored first brownish and then yellowish. In order to generate a sufficient amount of tetravalent cerium during the holding period, it is desirable to maintain the pH of the coating solution not too low. To control the pH, for example, it is advisable to appropriately adjust the amount of water-soluble epoxide added, which acts as an acid scavenger.

[0050] The process of the formation of tetravalent cerium can be monitored by the absorption spectrum from the ultraviolet to the visible range. For example, the absorption edge of the coating solution in the ultraviolet range shifts to the long wavelength range as tetravalent cerium is formed. If aging is continued until this absorption edge is in the region of, for example, 350 nm or more, especially 360 nm or more, a sufficient amount of tetravalent cerium is formed to form an easy-clean coating.

[0051] The preferred amount of the water-soluble epoxide to be added varies depending on the type, etc. When the water-soluble epoxide is propylene oxide, the mixing ratio of cerium (III) contained in the cerium compound to propylene oxide, expressed by molar ratio, is preferably in the range of 1:10 to 1:90, 1:15 to 1:80, further 1:20 to 1:70, and particularly 1:25 to 1:50.

[0052] After hydrolysis of the cerium compound, an epoxy group-containing organic compound such as a water-soluble epoxide may be further supplied. The epoxy group-containing organic compound may be supplied to the film to also clean the film. Supplying the epoxy group-containing organic compound after hydrolysis may contribute to the early stabilization of the water contact angle after film formation. It may also contribute to the improvement of the water contact angle after heat treatment.

[0053] The manufacturing method of this embodiment may further include a step of subjecting the glass substrate to a treatment accompanied by heating after forming an easy-clean coating on the glass substrate. The treatment accompanied by heating is at least one selected from the group consisting of the examples described above, and is particularly a heat bending treatment and / or an air-cooling tempering treatment. However, the glass substrate of this embodiment can also be used without undergoing such treatment.

[0054] The manufacturing method in this embodiment can also be implemented as a method including a step of applying a coating liquid containing chelated cerium ions onto a glass substrate to form a coating film on the glass substrate, and a step of drying the coating film. In order to chelate cerium ions, general chelating agents such as EDTA and acetylacetone can be used without particular limitation. The cerium ions in the coating liquid may be trivalent cerium. The chelated trivalent cerium ions are easily oxidized to tetravalent cerium ions at least in part in the drying step and further heat treatment step after the coating liquid is applied. The manufacturing method using chelation does not require the action of an acid scavenger such as a water-soluble epoxide, but can be implemented in the same manner as the above-mentioned method except for this point.

[0055] (Other manufacturing methods) The glass article with the easy-clean coating of this embodiment is not limited to the one produced by the liquid phase film-forming method exemplified above. The glass article with the easy-clean coating of this embodiment can also be produced by using a reduced pressure film-forming method, such as a sputtering method.

[0056] The present invention will be described in more detail below with reference to examples. However, the following examples are not intended to limit the present invention to a specific form.

[0057] First, the method for measuring the characteristics will be described. (Porosity) The optical parameters of the film were determined by spectral analysis of reflected light using an ellipsometer (Mizojiri Kogaku Co., Ltd., DVA-FL model). The laminated structure of the coated glass plate was set as glass plate (refractive index 1.52) / coating (refractive index 2.2; porosity 0), and the refractive index of the coating and film thickness were calculated by fitting, and the porosity was calculated.

[0058] (Optical properties) The visible light transmittance and the visible light reflectance were obtained from the visible and ultraviolet absorption spectrum measured with a spectrophotometer (Hitachi, Model 330), and the haze ratio was measured with a haze meter (Suga Test Instruments, Model HZ-V3).

[0059] (Water contact angle) The contact angle of water was measured using a contact angle measuring instrument (DMs-401, manufactured by Kyowa Interface Science Co., Ltd.) by dropping 4 mg of purified water onto the coating surface. The contact angle of water was measured after the coating was left in the air at room temperature for 20 days after film formation. The contact angle of water after heat treatment was measured when the coated glass plate was left in the air at room temperature for 40 days after heat treatment.

[0060] (Heat treatment) The coated glass plate was heated in an electric furnace set at 760℃ for 4 minutes, then removed from the furnace, wrapped in ceramic wool, and cooled to room temperature at a rate that would not cause thermal cracking. After the heat treatment, the water contact angle and other properties were measured.

[0061] (Stain adhesion test / tap water) The coated glass plate was held with its main surface facing vertically, and tap water was sprayed onto the coating surface. The glass plate was then kept in an atmosphere at 70°C for 10 minutes to allow the water droplets adhering to the coating surface to evaporate. After that, light from an LED light source was irradiated onto the edge of the coated glass plate, and the coating surface was observed.

[0062] (Stain adhesion test / hand soap) A commercially available hand soap (product name: Lion Kirei Kirei Medicinal Foam Hand Soap) diluted with water to a concentration of 20% by mass was dropped onto the coating surface of the coated glass plate, and the glass plate was then rotated so that the main surface was facing vertically, allowing the droplets to flow down along the coating surface. Tap water was then run over the surface for 5 seconds, and the extent to which the traces of the droplets had become thinner was confirmed. The coating surface was observed by shining light from an LED light source onto the edge of the coated glass plate, as described above.

[0063] Example 1 0.168 g of cerium (III) chloride heptahydrate (Sigma-Aldrich, 99.9%) was dissolved in 2 mL of anhydrous methanol (Sigma-Aldrich) to obtain a colorless and transparent cerium (III) chloride solution. This solution contains 9.6 mass% of cerium (III). Next, 1.75 g of the cerium (III) chloride solution and 0.859 g of propylene oxide (TIC, ≧99.0%) were mixed to obtain a stock solution. In this stock solution, the molar ratio of Ce to propylene oxide was 1:33.0. 2.609 g of the stock solution was diluted with 2.37 g of ethanol (Kanto Chemical, 99.5%) to obtain a coating solution. In this coating solution, CeCl 3 The concentration of cerium was 0.075 mmol / L. The coating solution was then aged by stirring overnight at room temperature. During aging, the coating solution changed from colorless and transparent to cloudy white, brown, and then pale yellow. Evaluation of the visible and ultraviolet absorption spectrum of the coating solution during aging confirmed that at least a portion of the trivalent cerium ions had been oxidized to tetravalent cerium ions.

[0064] A highly transparent glass (Optiwhite (registered trademark), 3 mm thick, manufactured by Nippon Sheet Glass Co., Ltd.) was cut into 10 cm squares, washed and dried to prepare a glass substrate. The aged coating liquid was applied to the glass substrate. The coating was performed using a spin coater (1H-360S model, manufactured by Mikasa Co., Ltd.) at a substrate rotation speed of 1000 rpm and a rotation retention time of 10 seconds after coating. The wet film obtained by applying the coating liquid was washed with isopropyl alcohol and further washed with acetone. The washed wet film was kept in an electric dryer set at 60°C to obtain a coated glass plate.

[0065] Example 2 A coated glass plate was obtained in the same manner as in Example 1, except that washing with acetone was replaced by washing with a 38% ethanol solution of cyclohexene oxide (manufactured by Fuji Photo Film, 95%).

[0066] Example 3 A coated glass plate was obtained in the same manner as in Example 1, except that the molar ratio of Ce to propylene oxide in the stock solution of Example 1 was changed to 1:65.7.

[0067] Example 4 The surface of the glass substrate used in Example 1 was coated with CeO 2 The CeO 2 A film was formed to obtain a coated glass plate.

[0068] Example 5 4.04 g of cerium (III) nitrate hexahydrate (Fujifilm Wako Pure Chemical Industries, Ltd.) was added to 268.8 g of a mixed solvent mainly composed of ethanol (Fine Eter A-10, manufactured by Futaba Chemical Industries, Ltd.), followed by 67.2 g of acetylacetone (manufactured by Tokyo Chemical Industry Co., Ltd.) and 60 g of propylene glycol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and the mixture was stirred for 24 hours in a constant temperature bath at 40°C to obtain a coating liquid.

[0069] A cleaned highly transparent glass (Optiwhite (registered trademark), 3 mm thick, manufactured by Nippon Sheet Glass Co., Ltd.) measuring 20 cm x 30 cm was prepared as a glass substrate. The coating liquid was applied to the glass substrate by spray coating. After air drying, the substrate was dried in an oven set at 250°C for 10 minutes, and then baked in a muffle furnace set at 760°C for 4 minutes to obtain a coated glass plate.

[0070] In Example 5, unlike Examples 1 to 3, aging of the coating liquid was not performed. However, in Example 5, since cerium was chelated with acetylacetone, cerium was oxidized during 10 minutes of drying and 4 minutes of baking to generate tetravalent cerium. The generation of tetravalent cerium can be confirmed, for example, by analyzing the coating film by X-ray photoelectron spectroscopy (XPS).

[0071] Example 6 A coated glass plate was obtained in the same manner as in Example 5, except that the spin coating method was carried out so as to obtain a thinner coating than in Example 5.

[0072] Example 7 A coated glass plate was obtained in the same manner as in Example 5, except that the spin coating method was carried out so as to obtain an even thinner coating than in Example 6.

[0073] Example 8 SiO as glass substrate 2 A glass plate on which the layer was formed (Pilkington OptiShower; SiO 2 A SiO 2 A coated glass plate was obtained in the same manner as in Example 5, except that a coating was formed on the layer.

[0074] Example 9 A coated glass plate was obtained in the same manner as in Example 5, except that a glass plate with a Low-E film was used as the glass substrate and a coating was formed on the Low-E film. The Low-E film was formed by depositing a 25 nm thick SnO 2 layer, 25 nm thick SiO 2 layer, 340 nm thick fluorine-doped SnO 2 This Low-E film was formed by a known method using the CVD method.

[0075] Comparative Example 1 A coated glass plate was obtained in the same manner as in Example 1, except that the molar ratio of Ce to propylene oxide in the stock solution of Example 1 was changed to 1:6.7.

[0076] Comparative Example 2 A coated glass plate was obtained in the same manner as in Example 1, except that the molar ratio of Ce to propylene oxide in the stock solution of Example 1 was 1:0, i.e., propylene oxide was not added.

[0077] Comparative Example 3 The glass substrate used in Example 1 was used as is. In other words, Comparative Example 3 is a glass plate without any coating. The water contact angle in this Comparative Example was measured after the glass plate was left in the air at room temperature for 20 days after cleaning, and after the above-mentioned heat treatment and left in the air at room temperature for 40 days.

[0078] [Table 1]

[0079] A pink interference color was observed in Example 4, but no interference color due to the coating was observed in the other Examples. In Example 1, the contact angle of water immediately after film formation was below 70°, but gradually increased. In contrast, in Example 2, a contact angle of 70° or more was measured immediately after film formation. In each Example, the contact angle of water was also measured 100 days after film formation and heat treatment, and in all cases the measured value was 70° or more and stable. Storage up to the 100th day was also performed in air at room temperature.

[0080] In Examples 2 and 3, the absorption edge of the absorption spectrum of the coating liquid shifted to the longer wavelength side during aging, as in Example 1. On the other hand, in Comparative Examples 1 and 2, no shift of the absorption edge to the longer wavelength side was observed during aging.

[0081] For Examples 1, 2, 4, and 5, the coating surfaces were observed using an SEM after the heat treatment. The results are shown in Figure 3 (Example 1), Figure 4 (Example 2), Figure 5 (Example 4), and Figure 6 (Example 5). The coating surfaces of Examples 1 and 2 were substantially flat, but had minute irregularities due to the cerium oxide microparticles present on the surface. It can be seen that more cerium oxide microparticles are present on the film surface of Example 2 (Figure 4) than in Example 1 (Figure 3).

[0082] SiO 2 In Examples 8 and 9, which used glass plates having a layer or the like formed as a base layer, the contact angle of water was lower than in Example 5, in which a coating was directly formed on the surface of the glass plate. This is believed to be because the diffusion and transfer of glass components from the glass plate to the coating was suppressed.

[0083] The crystallite size of the cerium oxide after heat treatment was measured using an X-ray diffraction method, and was 4.85 nm for Example 1 and 2.10 nm for Example 2. In Example 2, it is believed that the growth of the crystallites was inhibited by the added epoxy group-containing organic compound (cyclohexene oxide).

[0084] Example 10 A stain adhesion test using tap water was carried out on the coated glass plate produced in Example 1 (before heat treatment). The results are shown in FIG.

[0085] Example 11 A stain adhesion test using tap water was carried out on the coated glass plate produced in Example 4 (before heat treatment). The results are shown in FIG.

[0086] Comparative Example 4 A stain adhesion test / tap water was carried out on the glass plate of Comparative Example 3 (before heat treatment), i.e., a glass plate on which no coating was formed, and the results are shown in FIG.

[0087] Comparative Example 5 A coating was formed on the surface of the glass substrate used in Example 1 using an antifouling coating agent. Specifically, a coating agent was prepared by diluting Daikin Industries' "Optool DSX-E" with a solvent (3M's "Novec7200") to 0.1% by mass, and this was sprayed onto the surface of the glass substrate and dried to obtain a coated glass plate. Note that "Optool DSX-E" contains a fluoroalkyl group-containing compound as a water-repellent component at a concentration of 20% by mass. The contact angle of water on the surface of the obtained coating was 93°. A stain adhesion test / tap water was performed on this coated glass plate. The results are shown in FIG. 10.

[0088] Example 12 A stain adhesion test / hand soap test was carried out on the coated glass plate produced in Example 4 (before heat treatment). The observation results before washing with tap water are shown in Figure 11A, and the observation results after washing are shown in Figure 11B.

[0089] Comparative Example 6 A stain adhesion test / hand soap test was carried out on the glass plate of Comparative Example 3 (before heat treatment), i.e., a glass plate on which no coating was formed. The observation results before washing with tap water are shown in Fig. 12A, and the observation results after washing are shown in Fig. 12B.

[0090] Comparative Example 7 A stain adhesion test / hand soap was carried out on the coated glass plate produced in Comparative Example 5. The observation results before washing with tap water are shown in Fig. 13A, and the observation results after washing are shown in Fig. 13B.

[0091] In Comparative Example 4, ring-shaped stains (Fig. 9) were observed, while in Comparative Example 5, spot-shaped stains (Fig. 10) were observed. These stains were concentrated in specific areas of the coating surface, and therefore were easily observed. On the other hand, in Examples 10 and 11, the concentration of the remaining stains was reduced as the water droplets evaporated, and they became less visible (Figs. 7 and 8). The remaining stains in Examples 10 and 11 could be easily removed by wiping with a cotton cloth, but the stains in Comparative Examples 4 and 5 remained even when wiped with a cotton cloth.

[0092] On the glass surface of Comparative Example 6 and the coating of the fluorine-containing organic compound of Comparative Example 7, dirt due to organic matter (such as surfactants contained in hand soap) (FIGS. 12A and 13A) could not be washed away by simply running tap water over them (FIGS. 12B and 13B). On the other hand, in Example 12, dirt due to adhesion of organic matter (FIG. 11A) was almost completely removed by simply running tap water over them (FIG. 11B).

Claims

1. A glass substrate and an easy-clean coating on the glass substrate, the coating comprises cerium oxide; The coating is a single layer or a multi-layer film, and if the coating is a multi-layer film, the coating has a layer containing cerium oxide as a top layer, the contact angle of water on the surface of the coating is between 60° and 130°, At least one selected from the group consisting of window glass, roof glass, bathroom glass, mirror, store glass, mobile device glass, and solar cell glass, A coated glass article.

2. The contact angle after exposing the glass article to a heat treatment at 760° C. for 4 minutes is 60° or more and 130° or less; 2. The glass article of claim 1.

3. The cerium oxide is CeO 2 Including, 3. The glass article according to claim 1 or 2.

4. The coating comprises 10% by weight or more of cerium oxide; The glass article according to any one of claims 1 to 3.

5. An undercoat layer is interposed between the glass substrate and the coating. The glass article according to any one of claims 1 to 4.

6. Visible light transmittance is in the range of 65% or more. The glass article according to any one of claims 1 to 5.

7. The thickness of the coating is in the range of 5 to 500 nm. The glass article according to any one of claims 1 to 6.

8. The glass substrate is a reinforced glass. The glass article according to any one of claims 1 to 7.

9. 1. A method for producing a coated glass article comprising a glass substrate and an easy-clean coating on the glass substrate, the method comprising: the coating comprises cerium oxide; the contact angle of water on the surface of the coating is between 60° and 130°, The manufacturing method includes: forming an easy-clean coating comprising cerium oxide on a glass substrate; and subjecting the glass substrate on which the coating is formed to a treatment involving heating. A method for making a coated glass article.

10. The manufacturing method according to claim 9, wherein the treatment involving heating is at least one treatment selected from the group consisting of bending, air-cooling, chemical strengthening, laminating, multi-layer processing, and coating formation.

Citation Information

Patent Citations

  • Photocatalytic substrate active under visible light

    JP2007532462A

  • Article having water-repellent surface

    JP2008119924A

  • Glass or glass-ceramic products having a low-energy layer with high-temperature stability

    JP2013543833A

  • Transparent substrate with durable hydrophobic / oleophobic surface

    JP2014500163A

  • Substrate with repellent coating film and manufacturing method therefor

    JP2015116731A